RF32 The association between gestational weight gain and birthweight is partly self-fulfilling and should be interpreted with caution. (3rd September 2019) - Craig, Z; Harrison, W; Sørbye, LM; Stacey, T; Simpson, NAB; Nøhr, EA; Olsen, J; Ellison, GTH; Gilthorpe, MS; Tennant, PWG
Abstract : Background: The practice of routinely weighing pregnant women to monitor their 'weight gain' is controversial. In the United States, the National Academy of Medicine (NAM) advises regular weighing and recommends 'optimum' gain targets according to pre-pregnancy body mass index (BMI). In the United Kingdom, the National Institute for Health and Care Excellence (NICE) advises against routinely checking women's weight as pregnancy progresses. This quite radical difference hinges on the believed causal effect of 'gestational weight gain' (GWG) on adverse pregnancy outcomes, such as macrosomia (birthweight≥4 kg). However, estimating this is very difficult because some association is expected between GWG and birthweight, by definition, because the total maternal weight 'gain' implicitly includes the offspring's weight. This study sought to highlight this problem and explore the size of this 'tautological association' in simulated data. Methods: Data were simulated using DAGitty R 0.2–2 to reflect three causal scenarios: 1) Birthweight caused by maternal height alone, 2) Birthweight caused by maternal height and maternal pre-pregnancy weight 3) Birthweight caused by maternal height, maternal pre-pregnancy weight, and maternal net end-of-pregnancy weight (i.e. 'gain'). GWG was constructed from [maternal net end-of-pregnancy weight + birthweight]-[maternal pre-pregnancy weight]. The odds ratios (ORs) for macrosomia by GWG were estimated by logistic regression, with and without conditioning on maternal pre-pregnancy BMI, constructed from [maternal pre-pregnancy weight]/[maternal height] 2 . Simulation parameters were informed by full and partial correlations observed in the Danish National Birth Cohort. Results: Large associations were observed between GWG and macrosomia in all three scenarios, even though weight 'gain' only caused birthweight in the third scenario. The crude OR (95% credible interval) of macrosomia for GWG 'above' NAM guidelines compared with 'recommended' GWG were 1.26 (1.17–1.36), 1.34 (1.24–1.45) and 1.52 (1.41–1.65) respectively for scenarios 1 (birthweight caused by height only), 2 (height and pre-pregnancy weight), and 3 (height, pre-pregnancy weight, and end-of-pregnancy weight). Adjustment for pre-pregnancy BMI only modestly changed these associations, with ORs of 1.27 (1.18–1.37), 1.28 (1.19–1.39), and 1.42 (1.32–1.54) respectively. Conclusion: The apparent causal effect of maternal net weight 'gain' on birthweight (and hence macrosomia) is difficult to identify because the total maternal weight gain observed includes that of the offspring. A tautological association is therefore observed even when maternal weight has no causal effect on birthweight. Existing evidence regarding the 'effect' of GWG on birthweight should therefore be viewed with caution and should not be used to inform guidelines on 'ideal' gains in weight.